Persistence of Neuronal Alterations in Alcohol-Dependent Patients at Conclusion of the Gold Standard Withdrawal Treatment: Evidence From ERPs - Kuntz, André; Missonnier, Pascal; Prévot, Anne; Favre, Grégoire; Herrmann, François R.; Debatisse, Damien; Merlo, Marco C. G.; Gothuey, Isabelle (Frontiers in Psychiatry, 2021)
Background: This study using alcoholic patients and healthy controls contributes to the current debate about the efficacy of rehabilitation, in the context of alcohol withdrawal and relapse prevention. Specifically, alcohol detoxification has been associated with the recovery of cognitive abilities, strongly suggesting an adapted recruitment of neural bases of cognitive functions at completion of the treatment. To address this issue, we investigated the efficacy of the rehabilitation treatment on the main stages of information processing, using tasks varying in difﬁculty during an auditory oddball target paradigm. Method: We examined in alcoholic patients the effects of the benzodiazepine-based standard detoxification program on electrophysiological brain responses at incoming (D0) and completion (D15) of the treatment, as compared to controls. Electroencephalography (EEG) was used to unveil differences in the event-related potential (ERP) components typical for the information processing, namely the N1, N2 and P3b components. Results: We demonstrate that the time-course and the intensity of brain processing events (N2 component) involved in allocation of attention remain impaired at the conclusion of the treatment. Conclusion: This reveals that, even if although clinical and neuropsychological scores returned to normal values, subtle neural bases alterations persisted after a 2-week treatment. This could be a marker of the risk of relapse in alcohol consumption.